Multi-terminal direct-current grids : modeling, analysis, and control - Chaudhuri, Nilanjan Ray, 1981- (IEEE / Wiley & Sons, Inc., 2014)
"Presents a comprehensive modeling framework for MTDC grids which is compatible with the standard AC system modeling for stability studies"--